ISLAMIC HIERARCHY OF VALUE: Abdullah Saeed’s progressive interpretation of the Qur’an - Rois, Choirur; Muchlis, Muchlis; Irfan, Agus; Anam, Hairul; Rusdi, Rusdi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
The interpretation of the Qur'an often neglects sociological disparities, despite its inherent social dimensions. This study examines Abdullah Saeed's progressive interpretation of the Qur'an, focusing on his concept of the Islamic hierarchy of values as a framework for recontextualizing ethical-legal injunctions in modernity. Employing a descriptive-qualitative method with a hermeneutic and socio-historical approach, this research traces the epistemological foundations of Saeed’s contextual exegesis and its implications for contemporary Qur’anic scholarship. Saeed argues that ethical-legal verses must be reinterpreted in light of evolving social realities, emphasizing a dynamic hierarchy of values that prioritizes the Qur'an's overarching moral objectives over rigid textual literalism. Influenced by Fazlur Rahman’s double-movement hermeneutics, Saeed systematically develops an interpretive model that distinguishes between timeless universal principles and time-bound rulings. His approach advocates for a shift from textualist to contextual methodologies, ensuring the Qur'an’s relevance to modern challenges. This study concludes that Saeed’s hierarchy of values offers a transformative framework for progressive Qur’anic interpretation, balancing fidelity to the text with responsiveness to societal change, thereby enriching contemporary Islamic thought.